CO2-, He- and H2-broadening coefficients of SO2 for ν1 band and ground state transitions for astrophysical applications. (December 2017) - Ceselin, Giorgia; Tasinato, Nicola; Puzzarini, Cristina; Pietropolli Charmet, Andrea; Stoppa, Paolo; Giorgianni, Santi
Abstract: The discovery of the Universe and of the interstellar medium (ISM) is based on the knowledge of the molecules that are present in those places. Most of our understanding about the composition of the ISM and planetary atmospheres has been made possible almost entirely thanks to spectroscopic observations. Sulfur dioxide, SO2, is one of the about 200 molecules that have been detected in the ISM or circumstellar shells. In addition to its astrophysical relevance, SO2 has a proved role in the Earth's atmosphere. It origins from biomass burning and volcanic eruptions and directly enters in the sulfur cycle. In this work high-resolution tunable diode laser (TDL) infrared (IR) spectroscopy and mm-/sub-mm wave spectroscopy are exploited to retrieve the broadening parameters of sulfur dioxide perturbed by H2, He and CO2 . IR measurements are carried out for ν 1 band transitions around 9 μm by using He and CO2 as damping gases. As far as the vibrational ground state is concerned, about 20 rotational transitions are analyzed by means of the speed dependent Voigt profile to retrieve H2 - and He-broadening coefficients. From the experimental results some conclusions about the quantum number dependence of the H2 -, CO2 - and He-collisional cross sections are drawn. Both IR and MW experiments highlight a very weak dependence of He broadening parameters on the K a and J rotational quantum numbers. In a similar way, also SO2 -H2 broadening coefficients show a negligible dependence on the rotational quantum numbers. Conversely, when CO2 is employed as perturbing species, the observed collisional cross sections tend to decrease with increasing K a values and to increase against J, at least over the range of quantum numbers considered. The present results provide the first systematic determination of line-by-line SO2 -CO2 broadening coefficients and they are of relevance to increase the potential use of spectroscopic databases for astronomical applications. Highlights: SO2 molecule of astrochemical and atmospheric relevance. Determination of broadening coefficients of SO2 perturbed by CO2, He and H2 . Experiments performed in the infrared and microwave regions. First extensive determination of line-by-line SO2 -CO2 collisional cross section. Dependence of broadening parameters on J and K a rotational quantum numbers.